Contributions of ethnobiology to the conservation of tropical rivers and streams - Silvano, R. A. M.; Silva, A. L. [UNESP]; Ceroni, M.; Begossi, A. (John Wiley & Sons Ltd, 2008)
1. This study aimed to link basic ethnobiological research on local ecological knowledge (LEK) to the conservation of Brazilian streams, based on two case studies: original data on LEK of fishermen about freshwater fish in the Negro River, Amazon, and previously published data about LEK of farmers on the ecological relationship between forest and streams in the Macabuzinho catchment, Atlantic Forest.2. Information was obtained from fishermen through interviews using standard questionnaires containing open-ended questions. Informants for interview were selected either following some defined criteria or applying the 'snowball' method.3. Fishermen's LEK about the diets and habitats of 14 fish species in the Negro River provided new biological information on plant species that are eaten by fish, in addition to confirming some ecological patterns from the biological literature, such as dependence of fish on forests as food sources.4. In the Atlantic Forest, a comparison between farmers' LEK and a rapid stream assessment in the farmers' properties indicated that farmers tended to overestimate the ecological integrity of their streams. Farmers recognized at least 11 forest attributes that correspond to the scientific concept of ecosystem services. Such information may be useful to promote or enhance dialogue among farmers, scientists and managers.5. These results may contribute to the devising of ecosystem management measures in the Negro River, aimed to conserve both rivers and their associated floodplain forests, involving local fishermen. In the Atlantic Forest, we proposed some initiatives, such as to allow direct economic use of their forests to conciliate conflicting perceptions of farmers about ecological benefits versus economic losses from reforestation. Despite their cultural, environmental and geographical differences, the two study cases are complementary and cost-effective and promising approaches to including LEK in the design of ecological research. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: local ecological knowledge; fish ecology; floodplain forests; ecosystem services; fishermen; farmers; Atlantic Forest; Amazon